CLEAN : CO2 large-scale enhanced gas recovery in the Altmark Natural Gas Field -- GEOTECHNOLOGIEN science report no. 19 - Kuhn, Michael; Munch, Ute. (Berlin : Springer, 2013)
The project CLEAN (CO2 Large-Scale Enhanced Gas Recovery in the Altmark Natural Gas Field) provides site specific knowledge for a potential future pilot project. This contributed volume gives an overview and final results of the entire project which is finalized to the end of 2012.
1. Introduction to the joint research project CLEAN: CO2 Large-scale Enhanced gas recovery in the Altmark Natural gas fields -- 2. Technical Aspects of CO2 Injection -- 3. Well Integrity -- 4. Evaluation of Geo-Processes -- 5. Reservoir and Cap Rock Monitoring -- 6. Environmental and Process Monitoring -- 7. Theoretical test case of the injection of 100,000 t of CO2 into the Altmark depleted gas field -- 8. Public Outreach.
Includes bibliographical references and index.
Keywords: Geological carbon sequestration; Gas reservoirs; Natural gas